Proof by Mathematical Induction: Sum of Integers
Goal
Prove that (1 + 2 + 3 + \ldots + n = \frac{n(n+1)}{2}) for all integers (n \geq 1).
Steps in the Proof
1. Base Case
- Definition: The simplest case to verify the statement.
- Case: (n = 1)
- Left-hand side (LHS): (1)
- Right-hand side (RHS): (\frac{1(1+1)}{2} = \frac{2}{2} = 1)
- Verification: LHS = RHS, so the base case holds true.
2. Induction Hypothesis
- Assumption: Assume the statement is true for (n = k).
- (1 + 2 + 3 + \ldots + k = \frac{k(k+1)}{2})
3. Induction Step
- Goal: Prove the statement for (n = k + 1).
- Setup: Start with the left-hand side for (n = k + 1):
- (1 + 2 + 3 + \ldots + k + (k+1))
- Use Hypothesis: Replace the sum up to (k) using the hypothesis:
- (\frac{k(k+1)}{2} + (k+1))
- Common Denominator:
- Multiply ((k+1)) by (\frac{2}{2}) to combine terms:
- (\frac{k(k+1)}{2} + \frac{2(k+1)}{2} = \frac{k(k+1) + 2(k+1)}{2})
4. Simplifying the Expression
- Distribute:
- (k(k+1) + 2(k+1) = k^2 + k + 2k + 2)
- Combine like terms: (k^2 + 3k + 2)
- Right-hand side for (k + 1):
- ((k+1)(k+2) = k^2 + 2k + k + 2)
- Simplifies to: (k^2 + 3k + 2)
5. Verification
- Equality: Both sides simplify to (k^2 + 3k + 2), proving equal numerators.
- Conclusion: Given LHS = RHS for (n = k + 1), the proof holds.
Conclusion
- By induction, the statement holds for all (n \geq 1).
- Successfully proved (1 + 2 + 3 + \ldots + n = \frac{n(n+1)}{2}).
Additional Information
- Stay tuned for more math tutorials from Learn Math Tutorials.
- Subscribe for more educational content!